Orally Delivered Sour Cherry Seed Extract (SCSE) Affects Cardiovascular and Hematological Parameters in Humans. (9th January 2015) - Csiki, Zoltan; Papp‐Bata, Agnes; Czompa, Attila; Nagy, Aniko; Bak, Istvan; Lekli, Istvan; Javor, Andras; Haines, David D.; Balla, Gyorgy; Tosaki, Arpad
<x xml:space="preserve">Abstract</x> In the present study, we investigated the effects of sour cherry seed extract (SCSE) on a variety of systemic processes that contribute to general health and viability of human subjects. The experiments were conducted according to a double‐blind protocol in which six healthy individuals were administered 250‐mg/day SCSE for 14 days, while four were treated with placebo. Peripheral blood was collected before and after the treatment period. Samples were analyzed for levels of selected cells, enzymes, or metabolites. Subjects that received SCSE showed increases in the values of mean cell volume, serum transferrin, mean peroxidase index, and representation of peripheral blood lymphocytes. On the other hand, decreases were observed in circulating neutrophils and ferritin levels. Changes observed in the present study do not fit into a clear pattern that might yield additional in‐depth understanding of SCSE‐mediated alterations in physiologic responses. The most encouraging result of the present study is the absence of any indication of toxicity by subjects consuming the extract. Copyright © 2015 John Wiley & Sons, Ltd.